Structural health monitoring of composite structures using fiber optic methods - Rajan, Ginu; Prusty, B. Gangadhara (Devices, circuits, and systems, 2016)
This highly comprehensive, introductory book explains the basics of structural health monitoring aspects of composite structures. This book serve as an all-in-one reference book in which the reader can receive a basic understanding of composite materials, manufacturing methods, the latest types of optical fiber sensors used for structural health monitoring of composite structures, and demonstrated applications of the use of fiber sensors in a variety of composite material structures. The content draws upon the authors' and distinguished contributors' extensive research/teaching and industrial experience to fully cover the structural health monitoring of composite materials using fiber optic sensing methods.